2012
DOI: 10.1080/15459624.2012.723584
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Resistance of Disposable Nitrile Gloves Exposed to Simulated Movement

Abstract: Large discrepancies between laboratory permeation testing and field exposures have been reported, with indications that hand movement could account for a portion of these differences. This study evaluated the influence of simulated movement on chemical permeation of 30 different disposable nitrile glove products. Products were investigated out-of-box and with exposure to simulated whole-glove movement. Permeation testing was conducted using ethanol as a surrogate test chemical. A previously designed pneumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…(2) Phalen and Wong reported comparable results with up to a 33% decrease in BT and up to a 78% increase in SSPR with exposure to simulated whole-glove movement. (2) A 3-fold increase in cumulative exposure, as the area under the permeation curve at 30 min (AUC 30 ), was also reported, which does not directly compare with the 1-fold increase in CP 30 in this current study. It has been shown that area under the permeation curve can provide an improved estimate of worker exposure over time; (2) however, both AUC 30 and CP 30 are a function of the BT and SSPR.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…(2) Phalen and Wong reported comparable results with up to a 33% decrease in BT and up to a 78% increase in SSPR with exposure to simulated whole-glove movement. (2) A 3-fold increase in cumulative exposure, as the area under the permeation curve at 30 min (AUC 30 ), was also reported, which does not directly compare with the 1-fold increase in CP 30 in this current study. It has been shown that area under the permeation curve can provide an improved estimate of worker exposure over time; (2) however, both AUC 30 and CP 30 are a function of the BT and SSPR.…”
Section: Discussionmentioning
confidence: 87%
“…These results are consistent with a similar study evaluating the effect of movement on the permeation of ethyl alcohol through disposable nitrile gloves. (2) Phalen and Wong reported comparable results with up to a 33% decrease in BT and up to a 78% increase in SSPR with exposure to simulated whole-glove movement. (2) A 3-fold increase in cumulative exposure, as the area under the permeation curve at 30 min (AUC 30 ), was also reported, which does not directly compare with the 1-fold increase in CP 30 in this current study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations